ANALISIS KELAYAKAN FINANSIAL PEMBIBITAN KAMBING (STUDI KASUS PETERNAK SKALA MIKRO DAN KECIL) DI PROVINSI LAMPUNG - Reli Hevrizen; Ktut Murniati; Zainal Abidin (Wahana Peternakan, 2023)
This study aims to analyze the financial feasibility of a goat breeding business on a micro-scale farm Tanggamus Regency and a small-scale farm South Lampung. The data used in this study are primary and secondary data obtained through interviews and literature studies. Financial analysis was measured by calculating Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), Internal Rate of Return (IRR), and Payback Period (PP). Based on the results of the analysis, it was concluded that micro and small scale livestock farming in the two research locations was declared feasible to continue. This feasibility is expressed by an NPV value greater than zero, which is Rp. 121,303,075 for micro-scale farm and Rp. 370,846,687 for small-scale farm. The IRR value which was greater than the discount rate was 30.41% for the micro scale and 50.7% for the small scale farm. Net B/C value > 1, 2.62 for micro scale and 4.20 for small scale farm. The payback period for micro-scale farm was 3 years and 5 months and for small-scale farm was 2 years and 2 months. Keywords: Financial Feasibility, Goat Breeding, Farmers